Evidence of multiple thermokarst lake generations from an 11 800-year-old permafrost core on the northern Seward Peninsula, Alaska - Lenz, Josefine; Wetterich, Sebastian; Jones, Benjamin M.; Meyer, Hanno; Bobrov, Anatoly; Grosse, Guido (Boreas, 2016)
Permafrost degradation influences the morphology, biogeochemical cycling and hydrology of Arctic landscapes over a range of time scales. To reconstruct temporal patterns of early to late Holocene permafrost and thermokarst dynamics, site-specific palaeo-records are needed. Here we present a multi-proxy study of a 350-cm-long permafrost core from a drained lake basin on the northern Seward Peninsula, Alaska, revealing Lateglacial to Holocene thermokarst lake dynamics in a central location of Beringia. Use of radiocarbon dating, micropalaeontology (ostracods and testaceans), sedimentology (grain-size analyses, magnetic susceptibility, tephra analyses), geochemistry (total nitrogen and carbon, total organic carbon, δ13Corg) and stable water isotopes (δ18O, δD, d excess) of ground ice allowed the reconstruction of several distinct thermokarst lake phases. These include a pre-lacustrine environment at the base of the core characterized by the Devil Mountain Maar tephra (22 800±280 cal. a BP, Unit A), which has vertically subsided in places due to subsequent development of a deep thermokarst lake that initiated around 11 800 cal. a BP (Unit B). At about 9000 cal. a BP this lake transitioned from a stable depositional environment to a very dynamic lake system (Unit C) characterized by fluctuating lake levels, potentially intermediate wetland development, and expansion and erosion of shore deposits. Complete drainage of this lake occurred at 1060 cal. a BP, including post-drainage sediment freezing from the top down to 154 cm and gradual accumulation of terrestrial peat (Unit D), as well as uniform upward talik refreezing. This core-based reconstruction of multiple thermokarst lake generations since 11 800 cal. a BP improves our understanding of the temporal scales of thermokarst lake development from initiation to drainage, demonstrates complex landscape evolution in the ice-rich permafrost regions of Central Beringia during the Lateglacial and Holocene, and enhances our understanding of biogeochemical cycles in thermokarst-affected regions of the Arctic.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bor.12186